1971
DOI: 10.1007/bf02310044
|View full text |Cite
|
Sign up to set email alerts
|

Sur la vascularisation du tuber postérieur chez l'homme et sur les relations vasculaires tubérohypophysaires

Abstract: R6sum6Le tuber post6rieur ou 6minenee post-infundibulaire contient une trame vasculaire form6e d'un r6seau superficiel et d'un r6seau profond. L'un et l'autre sont drain6s /~ la lois vers la circulation g6n6rale par des veines tub6riennes et vers le syst6me porte hypophysaire. II apparait ainsi que le systbme porte hypophysaire d6borde en arribre les limites de l'hypophyse pour atteindre directement le tuber. De plus, le plexus primaire du systbme porte qui oeeupe l'6minence m6diane ant6ro-lat6rale, est fortem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Previous immunohistochemical studies from our laboratory [10,63] showed a highly abundant network of KP-IR axons around the portal vasculature of the human postinfundibular eminence which contains a superficial and a deep portal capillary plexus [100]. These observations raise the possibility that, unlike in rodents, KP is secreted into the hypophysial portal circulation of the human as a hypophysiotropic factor.…”
Section: Connections Of Kp Neuronsmentioning
confidence: 68%
“…Previous immunohistochemical studies from our laboratory [10,63] showed a highly abundant network of KP-IR axons around the portal vasculature of the human postinfundibular eminence which contains a superficial and a deep portal capillary plexus [100]. These observations raise the possibility that, unlike in rodents, KP is secreted into the hypophysial portal circulation of the human as a hypophysiotropic factor.…”
Section: Connections Of Kp Neuronsmentioning
confidence: 68%
“…These GnRH projections were present in highest abundance in the postinfundibular eminence (fig. 1a-i) which contains a superficial and a deep plexus of hypophysial portal capillaries [45]. These capillary plexuses were surrounded by GnRH-IR axons and, at the same time, also by very dense KP-IR (fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that neuropeptides released from the varicosities of these axon plexuses reach the adenohypophysis via the short portal veins to influence gonadotroph functions. In addition, the secreted neuropeptides might directly enter the systemic circulation from the portal capillary plexuses of the postinfundibular eminence [45] and through the tuberal veins of the InfS. It is important to recognize that many neuropeptides present in the external zone of the sheep median eminence are not necessarily secreted in significant amounts into the hypophysial portal blood [54] and this can also be the case in primates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 best-prepared brains were used for photographs, measurements, and statistical analysis. All photographs were taken parallel (6) and anterior cerebral artery (ACAJ (7); c: two preoptic arteries (8) arising from ACA; d: preoptic artery and commissural arteries; e: preoptic artery (8) and optic branch (9) of ACA; f: preoptic artery (8) and supraoptic artery (10); g: supraoptic artery (10) and optic branch (11) of internal carotid artery (ICA) (12); h: right (13) and left (13') superior hypophyseal arteries (SHAs); i: superior (13) and inferior hypophyseal arteries (cut);y. two ipsilateral SHAs (13); k: collateral branches of same SHA (13'); 1: SHA (13) and optic branch (9); m: SHA (13') and tuberoinfundibular artery (14) arising from ICA (12); n: SHA (13) and tuberoinfundibular artery (15) arising from posterior communicating artery (PCoA) (16); o: two tuberoinfundibular branches (14) of ICA; p: tuberoinfundibular branch (14) and optic branch (11) of ICA; q: tuberoinfundibular branch (14) and PCoA (16); r: tuberoinfundibular branch (14) of ICA and tuberoinfundibular branch (15) of PCoA; s: tuberoinfundibular artery (15) and optic branch (11); t: tuberoinfundibular artery (15) and PCoA (16); u: collateral branches of tuberoinfundibular artery (15); v: two ipsilateral tuberoinfundibular arteries (15); w: two contralateral tuberoinfundibular arteries; x: tuberoinfundibular artery (15) and mamillary branch (17) of PCoA; y: tuberoinfundibular artery (15) and mamillary ...…”
Section: Methodsmentioning
confidence: 99%